Analysis on the characteristics of eye movement and the evaluation of psychological perception for forest waterscape space. Issue 1 (January 2021) - Gao, Y; Sun, X M; Zhang, T; Zhan, H
Abstract: For landscape architects, how to provide a highly quality forest landscape for visitors has always been an important topic. This study based on the results of previous field observation, combined with eye tracking technology and psychological perception questionnaire, and used the Wilcoxon rank sum test, T test and Spearman's rho correlation analysis in SPSS 23.0 to statistically analyze the data. The main purpose is to clarify the relationship between visual behavior characteristics and psychological perception evaluation of the forest waterscape space where tourists have more behavioral evaluations during forest walk. Main results are as follows: 1. There are differences eye movement behaviors of different types of forest waterscape space, especially in the visual span; 2. There are significant differences visitor's psychological evaluation of different types of forest waterscape in five indices, which in whether the landscape content is changing, whether the color is rich, whether the color is bright, whether the space is open and whether you can see the distant landscape; 3. There is a correlation between human eye movement behavior and psychological perception evaluation in different types of forest waterscape spaces. The scenes with a large number of fixations also have higher satisfaction, and fixations count have positively correlated with the spatial perception evaluation results, which including plant diversity, landscape richness, permeability and the layering. That is to say, richness of landscape elements and color, permeability of the space and the regularity of the forest waterscape space affect the participants' eye movement observation mode. Through the above analysis, we suggest that in the planning and design of forest waterscape space should be considerate the characteristics of different landscape elements, meanwhile we should pay attention to the interspersion of appropriate heterogeneous landscape space.